The effects of local and landscape context on leafhopper (Hemiptera: cicadellinae) communities in coffeee agroforestry systeMON of Costa Rica - Ramos, M. (2008)
Tesis (Ph. D) -- CATIE, Turrialba (Costa Rica), 2008